2017
DOI: 10.4048/jbc.2017.20.3.264
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathologic Characteristics of Pregnancy-Associated Breast Cancer: Results of Analysis of a Nationwide Breast Cancer Registry Database

Abstract: PurposeThis study aimed to evaluate the clinicopathological characteristics of pregnancy-associated breast cancer (PABC) in comparison with non-pregnancy associated breast cancer (non-PABC).MethodsA total of 344 eligible patients with PABC were identified in the Korean Breast Cancer Society Registry database. PABC was defined as ductal carcinoma in situ, invasive ductal carcinoma, or invasive lobular carcinoma diagnosed during pregnancy or within 1 year after the birth of a child. Patients with non-PABC were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
32
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 9 publications
2
32
0
Order By: Relevance
“…Compared to nulliparous women, women with PABC, especially those diagnosed in the first year after delivery, presented a more advanced and aggressive stage of cancer and higher proportions of ER − , PR − , HER2 + and triple‐negative tumors . Hormone receptor‐negative cells were frequently observed in PABC patients compared to those in non‐PABC patients . PABC remains an understudied but important and growing clinical problem worldwide.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to nulliparous women, women with PABC, especially those diagnosed in the first year after delivery, presented a more advanced and aggressive stage of cancer and higher proportions of ER − , PR − , HER2 + and triple‐negative tumors . Hormone receptor‐negative cells were frequently observed in PABC patients compared to those in non‐PABC patients . PABC remains an understudied but important and growing clinical problem worldwide.…”
Section: Discussionmentioning
confidence: 99%
“…Only three East Asian studies have examined this problem . One study collected data from a hospital in northern Taiwan from 2004 to 2009 .…”
Section: Introductionmentioning
confidence: 99%
“…Those who had a full‐term pregnancy in the previous 5 years had a 1.62‐times higher risk of breast cancer recurrence. Finally, a Korean study identified 344 breast cancer patients, including ductal carcinoma in situ, diagnosed during pregnancy or within 1 year after delivery and 668 age‐, operation‐, and stage matched nonpregnancy‐related breast cancer patients treated between 1989 and 2012 . The authors found a significantly lower survival rate for pregnancy‐related breast cancer patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The survival rates of the PABC patients compared to those of the non-PABC patients were conflicting. Most studies [8,9,15,10,14,[16][17][18][19][20][21][22]] demonstrated a worse prognosis in PABC after excluding prognostic factors, including age, the tumor size, and lymph node status, while eight studies [23][24][25][26][27][28][29][30] showed no difference in survival between PABC and non-PABC patients after correcting for these factors.…”
Section: Discussionmentioning
confidence: 99%